(untitled) (Al-Academy, 2015)
The present research deals with the influencing factors which depends on the way perceptual of the graphic designer which enters in the design logos of the loco European health, where the search include four chapters, the researcher reviewed in the chapter 0ne the methodical frame of the research ,as reviewed in the second chapter the theoretical frame, and the previous studies which included three sections, the first section included the perceptual understandable and types of it, and the second section included the influencing factors in the designer perceptual ways and its division . While the third section included the perceptual in graphic designer through the percepted shapes and the relation with ground and colors for express the idea and the content of the art work and determine the formal organization which control in the perceptual field for the designer to embody, the designer idea and emerged from the theoretical from the indicators as scientific material which helped the researcher in her steps and her method for the research to analyzed five samples researchable content in chapter three which called steps chapter while the four chapter which the researcher arrived to it included the showing for the results recommendations and suggestions